Long-Term Effectiveness of Secukinumab in Patients with Axial Spondyloarthritis - Stefano Gentileschi; Donato Rigante; Jurgen Sota; Giuseppe Lopalco; Maria Grazia Giannotta; Giacomo Emmi; Gerardo Di Scala; Florenzo Iannone; Claudia Fabiani; Bruno Frediani; Luca Cantarini (Mediators of Inflammation)
Objectives. The primary aim of our study was to evaluate long-term efficacy of secukinumab (SCK) in patients with axial spondyloarthritis (axSpA); secondary aims were to evaluate drug retention rate and to identify differences in the clinical and laboratory assessment according to axSpA clinical features, dosage administered, and biologic treatment lines. Patients and Methods. We collected clinical, demographical, and treatment data from 39 patients affected by axSpA consecutively treated with SCK. Laboratory assessment was based on inflammation parameters; clinical assessment was performed with the Ankylosing Spondylitis Disease Activity Score- (ASDAS-) CRP and Bath Ankylosing Spondylitis Disease Activity Index (BASDAI). Data were recorded at baseline and every 3 months for the first year and then every 6 months in the second year. Results. Twelve males and 27 females were enrolled; both BASDAI and ASDAS-CRP showed a statistically significant reduction during the observation period (p<0.0001 and p<0.0001, respectively). C-reactive protein significantly decreased (p=0.006), with significant reduction at the post hoc analysis between baseline and both 6-month evaluation (p=0.02) and 24-month visit (p=0.036). No statistical significance was observed in BASDAI and ASDAS-CRP improvement (p=0.482 and p=0.164, respectively) between different dosages administered. No significant differences emerged in the BASDAI and ASDAS-CRP variations between biologic-naïve patients and subjects previously failing to tumour necrosis factor (TNF) inhibitors (p=0.53 and p=0.148, respectively). At the end of our observation, 7 out of 39 patients discontinued SCK. The global retention rate at the end of the study period was 78.2%, without any significant differences between biologic-naïve and anti-TNF-failure patients (p=0.619) or between subjects administered with different SCK dosages (p=0.614). No adverse events were reported. Conclusions. In our cohort, SCK has proved a remarkable effectiveness regardless biologic treatment line and dosages employed. As suggested by the notable drug retention rate, SCK has been able to maintain its effectiveness over a considerable long period of treatment.